Pemikiran Hukum Progresif Prof. Dr. Satjipto Rahardjo - Ahmad Faisal (edujavare, 2023)
The judiciary should not become the mouthpiece of the law by overriding the values of justice. In order to find the values of justice in every decision, judges should explore the values that live in society. Indonesian legal figure, Prof. Dr. Satcipto Rahardjo expressed progressive legal thinking that prioritizes the deepest meaning of the law, namely justice. This progressive legal theory needs to be studied in the midst of various kinds of judge decisions that are considered to be an obstacle to the achievement of the values of justice. By conducting a literature search, researchers interpreted and expressed arguments about the progressive legal theory put forward by Prof. Dr. Satcipto Rahardjo. The search results showed that he argued that judges are an important factor in determining whether the court is a place to seek victory or justice. For this reason, it is necessary to interpret progressive law to humanize the rigid law so that the law becomes alive and touches aspects of justice for the achievement of human happiness.